Karakteristik Pelaku Usaha Ikan Asin di Muara Angke - Nurfiqayumi Arnis; Burhanuddin Burhanuddin; Wahyu Budi Priyatna (Politeknik Negeri Lampung, 2018)
This study aims to analyze the characteristics of salted fish business in Muara Angke. This research was conducted in Muara Angke, North Jakarta, namely salted fish business. The salted fish business in Muara Angke is the largest fish and fish processing center in Jakarta. Data analysis in this research is qualitative and quantitative. Qualitative analysis using descriptive method to menggambarkandan describe the characteristics of salted fish business in Muara Angke. The results revealed that the characteristics of salted fish business in Muara Angke in general, among others: (1) The majority of businessmen of male sex and salted fish processing business is the main livelihood; (2) The education level of the majority of elementary school graduates; (3) they have sufficient experience in the processing of salted fish, (4) their income is mostly able to fulfill their daily needs (5) The business capital is obtained as personal capital; (6) the standard of living and welfare of salted fish farmers in general is still low, due to the small scale of business, and the majority of salted fish business is oriented only on the fulfillment of daily needs.Â Keywords: characteristic, salted fish, UMKM